The Development of Teacher Handbook on Preschool-Aged Children’s Aggressive Behavior and IT-Based Solutions - Titik Mulat Widyastuti; Puji Handayani (Universitas Ahmad Dahlan, 2019)
The current study aimed at developing a teacher handbook on preschool-aged children's aggressive behavior and its solution. The study was conducted in Kindergarten in Turi Subdistrict, Sleman, Yogyakarta. The subjects of the study were Kindergarten teachers, students, and parents. The data collection method consisted of interview, observation, and questionnaire. The present study was categorized as Research and Development (R&D). The study was conducted in six phases. Phase I involved survey and preliminary study, phase II involved prototyping of teacher handbook, phase III was initial evaluation, phase IV was product tryout, phase V was product revision, phase VI was the final product. The data were analyzed using quantitative analysis. Then it was converted into qualitative data by percentage formula in order to point out the product quality. The data were then analyzed using qualitative and quantitative descriptive method. The result of the study showed that the use of teacher handbook significantly affects the decrease in preschool-aged children's aggressive behavior. The result of paired sample t-test on the questionnaire score before and after the use of the teacher handbook was sig. (2-tailed) 0.000 < 0.05